Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Pendidikan Agama Islam - Susilowati, Evi (Center for Religious Studies and Social Empowerment Foundation, 2022)
This study aims to examine the implementation of the Independent Learning Curriculum in the formation of student character in Islamic religious education subjects. The main problem of this research is how is the realization of the Merdeka Learning Independent Campus curriculum in elementary schools? This research is a qualitative research with the method of observation, interviews and documentation. The results of the study indicate that the implementation of the independent learning curriculum in schools has been running but there are several obstacles faced by teachers in implementing it. Constraints related to understanding revolve around not understanding the essence of 'free learning,' it is difficult to get rid of the old habit of still dominating the lecture method. Other technical-related obstacles revolve around the difficulty of making teaching modules and the incompatibility of the learning platform with what is in it. Finally, at the evaluation stage, the teacher has difficulty in making an assessment or assessment. Penelitian ini bertujuan untuk mengkaji implementasi Kurikulum Merdeka Belajar dalam pembentukan karakter siswa pada mata pelajaran pendidikan agama Islam. Permasalahan utama penelitian ini adalah bagaimana realisasi kurikulum Merdeka Belajar Kampus Merdeka di sekolah dasar? Penelitian ini merupakan penelitian kualitatif dengan metode observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi kurikulum merdeka belajar di sekolah telah berjalan namun ada beberapa kendala yang dihadapi guru dalam mengimplementasikannya. Kendala yang terkait dengan pemahaman berkisar pada belum dipahaminya esensi ‘merdeka belajar,’ sulit untuk menghilangkan kebiasaan lama yakni masih mendominasinya metode ceramah. Kendala lain terkait teknis berkisar pada kesulitan untuk pembuatan modul ajar dan ketidaksesuaian platform belajar dengan apa yang ada di dalamnya. Akhirnya pada tahap evaluasi guru mengalami kesulitan dalam melakukan penilaian atau assesmen.